Surface properties and antimicrobial performance of copper coatings electrodeposited on 304 stainless steel / Nik Norziehana Che Isa - Che Isa, Nik Norziehana (2017)
Bacterial contamination resulted from frequently-touched surface materials is responsible in the acquisition of infection especially in hospital. The utilization of copper as antimicrobial touch surfaces offers a solution that can serve as an additional line of defense against pathogens. Copper is the first and currently the only one surface metal that has received registration from Environmental Protection Agency (EPA) as antimicrobial material which is capable to inhibit biofilms, retains the antimicrobial activity under typical indoor conditions. In this study, electrodeposition technique was used to coat copper on 304 stainless steel using 0.01 M Cu2+ solutions containing either uncomplexed CuSO4 or complexed Cu-EDTA based systems.